KEEFEKTIFAN METODE COOPERATIVE LEARNING TIPE JIGSAW PADA PEMBELAJARAN SAKUBUN IV (Penelitian Eksperimen Terhadap Mahasiswa Semester V Tahun Ajaran 2016/2017 Pendidikan Bahasa Jepang FKIP UR) - Dian Pranesti; Sri Wahyu Widiati; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this research is to find out the difference of student’s ability in writing Japanese essays (sakubun) after implementing cooperative learning type Jigsaw. The research is conducted using weak experimental type one group pre test post test design. The object of this research is 20 semester five students as the respondents. The sample is taken by using simple random sampling technique. Data collection was performed by giving test. The given test was writing Japanese essays (sakubun) with the topic “music”. The writer applies two tests, they are pre test and post test. Pre test is given before the students are taught by implementing Methods Jigsaw, and post test is given after the students are taught with Methods Jigsaw. This research is processed using statistical tests (T-test) to know whether Ha is accepted or not. Based on the data analysis, the average value of the pre-test was 66,5 while the average value post-test was 79,95. This means the result of increased student essay.s Besides that, most students agree that this method is effectively helping to write Japanese essays (sakubun) easily. The result of this research is that there is a significant impact of using Method Jigsaw in learning of Japanese essays (sakubun) on the semester five students of Japanese Education Department Education Riau University. Keywords: Sakubun, Method Jigsaw, Writing Skill